Geographic Information Retrieval using Query Aware Document Ranking Method Case Study for Surakarta - M, Viny Christanti; Tionardi, Steven; Dewayani, Ery (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
This paper discusses the development of a Geographic Information Retrieval for Surakarta City in Indonesia. Surakarta City was chosen as the location of the place in the system because Surakarta got an award for the best tourist spot in Indonesia. In this case, Geographic Information Retrieval is a system that can handle geographic data by analyzing existing text data and generate output that can be used as decision-making on problems related to geographical. The method used in processing the information is Query Aware Document Ranking. The purpose of using this method is to provide relevant results such as output answer, answer’s images and coordinates of the answer.